Considerations in the Management of Giant Frontal Mucoceles with Significant Intracranial Extension: A Systematic Review. Issue 4 (July 2016) - Stokken, Janalee; Wali, Eisha; Woodard, Troy; Recinos, Pablo F.; Sindwani, Raj
Background: Giant frontal mucoceles, characterized by significant intracranial and/or intraorbital extension, can present with significant neurologic symptoms. Although typical mucoceles are managed endoscopically, giant mucoceles are often treated with an open or combined approach due to various concerns, including frontal lobe displacement, size, and rapid decompression of the intracranial component. The impact of significant intracranial extension on outcomes is not well described. Objective: This review studied key neurologic considerations in the management of giant frontal sinus mucoceles and analyzed outcomes of different management strategies. Methods: Systematic literature review by following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Results: Thirty-two articles, which represented 85 cases, met inclusion criteria. Neurologic symptoms on presentation ranged from headache (24.7%) and vision loss (12.9%) to extremity weakness (1.2%), frontal lobe syndrome (2.4%), and seizures (4.7%). Twenty-eight patients were treated endoscopically (34.1%), and 54 (65.9%) were treated with an external approach. Twenty-five of the open procedures included a craniotomy. Indications for the open approach included subdural empyema, enucleation, or large anterior table defects. Perioperative antibiotics were not consistently used. No perioperative seizures were reported with any approach. There were six cerebrospinal fluid leaks, all in the patients who underwent open procedures. The overall recurrence rate was 3.5%, with no recurrences reported in patients treated with an open approach. Follow-up ranged from 1 week to 8 years. Conclusions: Giant frontal mucoceles often present with various neurologic symptoms. Both open and endoscopic techniques offer excellent results. Endoscopic management is effective and preferred, except in special circumstances. An interdisciplinary team approach should be used to optimize surgical planning.